2020
DOI: 10.1136/jim-2020-001328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ischemic Postconditioning on Cell Apoptosis and Expression of Relevant Genes in Non-Culprit Coronary Arteries

Abstract: This study was performed to determine the effect of ischemic postconditioning on cell apoptosis and angiotensin II receptor type 1 (AT1), connexin 43 (Cx43), and β-tubulin mRNA expression in non-culprit arteries. Non-culprit arterial tissues were isolated from a rabbit myocardial ischemia-reperfusion model and randomly divided into sham, ischemia-reperfusion, and ischemic postconditioning groups. Cell apoptosis was detected by terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) staining. Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Our previous studies have shown that IP could significantly affect the expression of mRNA angiotensin II receptor type 1 (AT1), connexin 43 (Cx43), and β-tubulin, which are key factors in regulating the state of blood vessels and play an important role in nonculprit lesions in the patients with MI [ 13 ]. Consistently, western blot assay showed that IR obviously upregulated the level of AT1, Cx43 and β-tubulin in nonculprit coronary arterial tissues; however, these increases of AT1 and Cx43 were notably alleviated by IP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have shown that IP could significantly affect the expression of mRNA angiotensin II receptor type 1 (AT1), connexin 43 (Cx43), and β-tubulin, which are key factors in regulating the state of blood vessels and play an important role in nonculprit lesions in the patients with MI [ 13 ]. Consistently, western blot assay showed that IR obviously upregulated the level of AT1, Cx43 and β-tubulin in nonculprit coronary arterial tissues; however, these increases of AT1 and Cx43 were notably alleviated by IP.…”
Section: Resultsmentioning
confidence: 99%
“…The acute myocardial ischemia animal model was constructed according to our previous published literature [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of the stimulation of AT1R may depend on the accessibility of the AT1R-associated protein (ATRAP), which is able to enhance the internalization of AT1R from the cell surface to cytoplasm and reduce the action of Ang II [74]. More recently, studies performed on non-culprit arteries harvested from the rabbit model of myocardial ischemia-reperfusion provided evidence that the expression of AT1R was higher in the ischemia-reperfusion group than in the sham group, but expressions of AT1R, connexin 43, and β-tubulin were lower in the ischemic postconditioning group than in the ischemia reperfusion group [75].…”
Section: Experimental Evidence For the Negative Role Of Ang II In The...mentioning
confidence: 99%
“…Postconditioning activates several cellular signalling pathways, such as those involved in apoptosis, oxidative stress, inflammatory responses, and mitochondrial function [ 9 ]. For example, extensive studies have reported that apoptosis induced by IRI can be attenuated by post-conditioning [ 10 ]. This may be beneficial for cardiomyocyte preservation and infarct size reduction.…”
Section: Introductionmentioning
confidence: 99%